A side-on Mn(iii)–peroxo supported by a non-heme pentadentate N3Py2 ligand: synthesis, characterization and reactivity studies. Issue 8 (3rd February 2021) - Narulkar, Dattaprasad D.; Ansari, Azaj; Vardhaman, Anil Kumar; Harmalkar, Sarvesh S.; Lingamallu, Giribabu; Dhavale, Vishal M.; Sankaralingam, Muniyandi; Das, Sandip; Kumar, Pankaj; Dhuri, Sunder N.
Abstract : A new non-heme Mn(iii )–peroxo (1a ) has been generated, characterized and reactivity is in aldehyde deformylation reaction. A nucleophilic reactivity of 1a in aldehyde oxidation is proposed. Abstract : A mononuclear manganese(iii )–peroxo complex [Mn III (N3 Py2 )(O2 )] + (1a ) bearing a non-heme N, N ′-dimethyl- N -(2-(methyl(pyridin-2-ylmethyl)amino)ethyl)- N ′-(pyridin-2-ylmethyl)ethane-1, 2-diamine (N3 Py2 ) ligand was synthesized by the reaction of [Mn(N3 Py2 )(H2 O)](ClO4 )2 (1 ) with hydrogen peroxide and triethylamine in CH3 CN at 25 °C. The reactivity of 1a in aldehyde deformylation using 2-phenyl propionaldehyde (2-PPA) was studied and the reaction kinetics was monitored by UV-visible spectroscopy. A kinetic isotope effect (KIE) = 1.7 was obtained in the reaction of 1a with 2-PPA and α-[D1 ]-PPA, suggesting nucleophilic character of 1a . The activation parameters Δ H ‡ and Δ S ‡ were determined using the Eyring plot while E a was obtained from the Arrhenius equation by performing the reaction between 288 and 303 K. Hammett constants ( σ p ) of para -substituted benzaldehydes p -X-Ph-CHO (X = Cl, F, H, and Me) were linear with a slope ( ρ ) = 3.0. Computational study suggested that the side-on structure of 1a is more favored over the end-on structure and facilitates the reactivity of 1a .